Dehumanization during Delivery: Meanings and Experiences of Women Cared for in the Medellín Public Network - Cristina María Mejía Merino (Universidad de Antioquia, 2018)
Objective. This work sought to describe the meanings constructed in the experiences of women in relation to the care received by the healthcare staff at the moment of delivery.